2017
DOI: 10.3819/ccbr.2017.120004
|View full text |Cite
|
Sign up to set email alerts
|

Consonance Processing in the Absence of Relevant Experience: Evidence from Nonhuman Animals

Abstract: Consonance is a major feature in harmonic music that has been related to how pleasant a sound is perceived. Consonant chords are defined by simple frequency ratios between their composing tones, whereas dissonant chords are defined by more complex frequency ratios. The extent to which such simple ratios in consonant chords could give rise to preferences and processing advantages for consonance over dissonance has generated much research. Additionally, there is mounting evidence for a role of experience in cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Apparently, a more consonant sensory context, similarly to a low-entropy sensory context, induces the brain to estimate the inputs as more reliable (Quiroga-Martinez et al, 2019). It has also been suggested that our auditory cortices are generally more tuned to process consonant sounds (Bowling & Purves, 2015;Bowling et al, 2017) due to the similarity with human vocalizations (Crespo-Bojorque & Toro, 2016;Toro & Crespo-Bojorque, 2017). However, personal experiences, as musical training and listening, seem to be able to modulate these general trends (Crespo-Bojorque et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, a more consonant sensory context, similarly to a low-entropy sensory context, induces the brain to estimate the inputs as more reliable (Quiroga-Martinez et al, 2019). It has also been suggested that our auditory cortices are generally more tuned to process consonant sounds (Bowling & Purves, 2015;Bowling et al, 2017) due to the similarity with human vocalizations (Crespo-Bojorque & Toro, 2016;Toro & Crespo-Bojorque, 2017). However, personal experiences, as musical training and listening, seem to be able to modulate these general trends (Crespo-Bojorque et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that bird vocalizations as well as human voices are often composed of consonant sounds and that vocal similarity explains the aesthetic preference for consonance (Bowling et al, 2017). In accordance with this view, it is possible that the human nervous system might be specifically tuned by evolution to process such input (Crespo-Bojorque & Toro, 2016;González-García et al, 2016; J o u r n a l P r e -p r o o f Toro & Crespo-Bojorque, 2017;Tramo et al, 2006;Zentner & Kagan, 1996). This may represent a possible explanation of the greater precision estimation granted to consonant rather than dissonant sounds (Bowling and Purves, 2015).…”
Section: How To Build Precise Predictions? Evolutionary-based Vs Expmentioning
confidence: 94%
“…In a society where basic forms of group chorusing (proto-songs?) start to appear in the context of social rhythmic and coordinated behaviours, the interaction between the voice of male adults and women or children would tend to create octaves and fifths [ 34 ], provided there is a perceptual preference for these consonances which in fact does not seem to be unique to humans (for a review, see [ 194 ]). These group activities would start to promote, not only social bonding, but also group identity.…”
Section: Towards a Model For The Evolution Of Musicalitymentioning
confidence: 99%